GIZI DAN BUDAYA: EDUKASI PANGAN LOKAL BERBASIS MASYARAKAT DALAM KARANG ASAM FESTIVAL KABUPATEN MUARA ENIM - Putra, Decka Pratama; Yanti, Mery; Randi, Randi; Tresno, Tresno; Sununianti, Vieronica Varbi; Istiqoma, Istiqoma; Reftantia, Ghina (Jurnal AbdiMas Nusa Mandiri, 2026)
The shift in community consumption patterns toward fast food has led to a decline in the utilization of nutritious local foods. This community service activity aims to provide nutrition education based on a cultural festival to improve nutritional knowledge and increase public interest in consuming healthy local foods in Karang Asam Village, Muara Enim Regency. Academically, this activity contributes to the development of a community service method based on community-based participatory research (CBPR) that integrates aspects of health, culture, and community participation. The method employed a participatory approach with a cultural strategy through the annual Karang Asam Festival (KAF). The intervention was implemented through a Nutrition Education Zone and a Healthy Local Food Innovation Competition involving junior high school students. The evaluation was conducted using a pre-test and post-test design. The results indicate an increase in public interest in consuming healthy local foods, as well as greater awareness of the importance of preserving local food culture. These findings suggest that cultural festivals can serve as an effective medium for nutrition education.